Et in Arcadia ego, Et in Arcadia est. (4th April 2013) - Rhowbotham, Kevin
Abstract: Architect, academic and broadcasterKevin Rhowbotham scrutinises the reasoning and value of the New Pastoralism project. He dispels the Arcadian impulse as 'a specious and mythicised image of the rural', calling upon architects to seek a true understanding of rural conditions in relation to the urban.